Aβ1-42 increases the expression of neural KATP subunits Kir6.2/SUR1 via the NF-κB, p38 MAPK and PKC signal pathways in rat primary cholinergic neurons. (June 2019) - Li, Y; Ba, M; Du, Y; Xia, C; Tan, S; Ng, KP; Ma, G
ATP-sensitive potassium channels (KATP) may mediate a potential neuroprotective role in Alzheimer's disease (AD). Given that exposure to Aβ1-42 in cultured primary cholinergic neurons for 72 h significantly upregulates the expression of KATP subunits Kir6.2/SUR1, we aim to study the underlying signal transduction mechanisms that are involved in Aβ1–42 -induced upregulation of KATP subunits Kir6.2/SUR1. In the present study, we first identified the primary cultured rat cortical and hippocampal neurons using immunocytochemistry. 0.5 μM NF-κB inhibitor SN-50, 2 μM p38MAPK inhibitor SB203580 or 2 μM PKC inhibitor Chelerythrine chloride (CTC) were then added in three separate groups, followed by 2 μM Aβ1–42 30 min later in all 3 groups. Western Blot was performed 72 h later to detect the expression of KATP subunits Kir6.2/SUR1. We found that Aβ1–42 significantly increased the level of KATP subunits Kir6.2/SUR1 expression at 72 h when compared with the control group ( p < 0.05). However, when compared with the Aβ1–42 group, the level of KATP subunits Kir6.2/SUR1 expression at 72 h significantly decreased in the SN50 + Aβ1–42 group, SB203580 + Aβ1–42 group, and the CTC + Aβ1–42 group ( p < 0.05). Our findings suggest that the NF-κB, p38 MAPK, and PKC signal pathways are partially involved in the upregulation of KATP subunits Kir6.2/SUR1 expression induced by Aβ1–42 cytotoxicity in neurons, which supports a potential theoretical basis of targeting these signal pathways in the treatment of AD.